Initial clinical presentations and morphological characteristics of cerebral AVM in a tertiary health center – Does gender matter? - Jovian Philip Swatan; Wardah Rahmatul Islamiyah; Achmad Firdaus Sani; Dedy Kurniawan; Shakir Husain (World Neurosurgery: X, 2025)
Purpose: Comparative studies on the initial clinical presentation and morphological characteristics of cerebral arteriovenous malformation (AVM) between genders are limited. This study aims to analyze the influence of gender on these aspects. Materials and methods: We retrospectively analyzed our 8-year cerebral AVM database, covering the period from January 2016 to December 2023. The study included all patients diagnosed with cerebral AVM, who had no other vascular abnormalities and underwent a 3-dimensional cerebral digital subtraction angiography evaluation. We used bivariate analysis to compare the initial clinical presentations and morphological characteristics of cerebral AVM between genders. Results: The study included a total of 92 patients, comprising 53 males and 39 females. Male patients were more likely to present with seizures (p = 0.035, OR 2.52, 95 % CI 1.06–6.00), but less likely to present with headaches (p = 0.008, OR 0.32, 95 % CI 0.13–0.76). In terms of morphology, being male was significantly associated with a larger mean cerebral AVM size (p < 0.001), cerebral AVMs located in eloquent areas (p = 0.039; OR 2.81, 95 % CI 1.03–7.70), and a higher mean Spetzler-Martin grade (p = 0.015). Conclusion: This study highlights the influence of gender on the initial clinical presentation and morphological characteristics of cerebral AVM.